Policymaker perspectives on self-management of disease and disabilities using information and communication technologies - Amélie Gauthier-Beaupré; Bruno J. Battistini; Craig Kuziemsky; Jeffrey W. Jutai (Health Research Policy and Systems, 2023)
Abstract Background Policies that support health self-management are malleable and highly dependent on various factors that influence governments. Within a world that is shifting toward digitalization due to pressures such as the COVID-19 pandemic and labor shortages, policymaking on older adults’ self-management of chronic diseases and disability using information and communication technologies (ICTs) needs to be better understood. Using the province of Ontario, in Canada, as a case study, the research question was What is the environment that policymakers must navigate through in development and implementation of policies related to older adults’ self-management of disease and disability using information and communication technologies (ICTs)? Methods This study used a qualitative approach where public servants from 4 ministries within the government of Ontario were invited to participate in a 1-h, one-on-one, semi-structured interview. The audio-recorded interviews were based on an adapted model of the policy triangle, where the researcher asked questions about the influences from the different sources identified in the model. The interviews were later transcribed and analyzed using a deductive-inductive coding approach. Results Ten participants across 4 different Ministries participated in the interviews. Participants shared insights on various aspects of context, process and actors that help shape the current content of policies. The analysis revealed that policies, in the form of programs, services, legislation and regulations, are the result of collaborations and dialogue between different actors and get developed and implemented via a set of complex government processes. In addition, policy actions come from a plethora of sectors which all get influenced by several predictable and unpredictable external pressures. Conclusions The environment for policymaking in the government of Ontario regarding older adults’ self-management of disease and disability using ICTs is one that is mostly reactive to external pressures, while organized within a set of complex processes and multi-sectoral collaborations. The present research helped us to understand the complexity of policymaking on the topic and highlights the need for increased foresight and proactive policymaking, regardless of which governments are in-place.